2022
DOI: 10.1002/psp4.12785
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of mobocertinib in healthy volunteers and patients with non–small cell lung cancer

Abstract: Mobocertinib is an oral tyrosine kinase inhibitor approved for treatment of patients with locally advanced or metastatic non-small cell lung cancer (mNSCLC) with epidermal growth factor receptor gene (EGFR) exon 20 insertion mutations whose disease has progressed on or after platinum-based chemotherapy. This population pharmacokinetic (PK) analysis describes the PK of mobocertinib and its active metabolites, AP32960, and AP32914, using data from two phase I studies in healthy volunteers (n = 110) and two ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is believed that these two active metabolites do contribute to the observed efficacy of mobocertinib in patients [ 40 ]. Additionally, co-administration of mobocertinib with a strong CYP3A inhibitor increased its AUC by 527% while co-administration with a strong CYP3A inducer decreased its AUC by 95% [ 73 ]. Repeated dosing of mobocertinib was associated with lower-than-expected accumulation due to possible auto-induction of its metabolism via the CYP3A enzymes [ 74 ].…”
Section: Discovery and Optimization Of Mutant-selective Irreversible ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that these two active metabolites do contribute to the observed efficacy of mobocertinib in patients [ 40 ]. Additionally, co-administration of mobocertinib with a strong CYP3A inhibitor increased its AUC by 527% while co-administration with a strong CYP3A inducer decreased its AUC by 95% [ 73 ]. Repeated dosing of mobocertinib was associated with lower-than-expected accumulation due to possible auto-induction of its metabolism via the CYP3A enzymes [ 74 ].…”
Section: Discovery and Optimization Of Mutant-selective Irreversible ...mentioning
confidence: 99%
“…After a single oral dose of radiolabeled mobocertinib (160 mg), about 76% of the radioactivity was recovered in feces with ~6% as unchanged mobocertinib while about 4% was recovered in urine with ~1% as unchanged mobocertinib [ 72 , 73 ]. The amount of metabolites recovered in urine was low or below the limit of detection, suggesting that renal excretion is a minor pathway for its elimination [ 71 , 73 ].…”
Section: Discovery and Optimization Of Mutant-selective Irreversible ...mentioning
confidence: 99%
“…Modelbased simulations demonstrated that age, body weight, race, sex, creatinine clearance, estimated glomerular filtration rate, alanine aminotransferase, aspartate aminotransferase, bilirubin, and albumin did not have clinically meaningful effects on the systemic exposures of mobocertinib, AP32960, and AP32914 in patients with mNSCLC, suggesting that dose adjustment is not required based on these covariates. 7 The objective of this exposure-response analysis was to assess potential relationships between exposure to mobocertinib and its active metabolites (AP32960 and AP32914) with clinical ORRs, rates of selected AEs, and time to first dose reduction in patients with EGFRex20inspositive mNSCLC previously treated with platinum-based chemotherapy who received mobocertinib 160 mg q.d. utilizing data from the phase I/II study.…”
mentioning
confidence: 99%
“…An enzyme compartment with drug‐dependent stimulation of enzyme production (i.e., auto‐induction) was included to describe the observed nonlinear PK of the three moieties. Model‐based simulations demonstrated that age, body weight, race, sex, creatinine clearance, estimated glomerular filtration rate, alanine aminotransferase, aspartate aminotransferase, bilirubin, and albumin did not have clinically meaningful effects on the systemic exposures of mobocertinib, AP32960, and AP32914 in patients with mNSCLC, suggesting that dose adjustment is not required based on these covariates 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation